A Review of Recent Developments in Coating Systems for Hot-Dip Galvanized Steel - Yu, Zhen; Hu, Jiming; Meng, Huimin (Frontiers in Materials, 2020)
It is highly vital in automotive body, high-speed rail overhead line parts and water distribution systems to use hot-dip galvanized steel (HDGS) coatings for efficiency and ease of synthesis. Various novel coating systems could surpass the technical restrictions of traditional anticorrosion techniques. In consequence, inorganic or organic coating systems must be chosen accurately and suitably. Meanwhile, these coating systems should be evaluated in accordance with their unique material characteristics and synergistic electrochemical parameters. From this view, we summarize an overview of recent developments of anticorrosive coating systems researches for HDGS. First, we demonstrate the traditional protective coatings to match the use of HDGS. Likewise, emerging and state-of-the-art protective coatings are summarized as well. Subsequently, methods for the assessment criteria of traditional and emerging protective coatings are displayed and illustrated through electrochemical analysis. Concluding, we make a proposal about the future developments of protective coating systems for HDGS.